Alpha 1‐acid glycoprotein (orosomucoid) and plasma protein binding of quinine in falciparum malaria. - K. Silamut (2018)
1. Plasma concentrations of alpha 1‐acid glycoprotein (AAG) and plasma protein binding of quinine were measured in 97 Thai adults with acute falciparum malaria. There was a linear relationship between log AAG and percentage quinine binding (r = 0.71, P less than 0.001) in vivo, which was similar to that observed in vitro; the slopes and intercepts of the regression lines at AAG concentrations of 1 g l‐1 were −8.94 and −8.41, and 7.2% and 10.9%, respectively. 2. Hill plots from these data suggest a single high affinity quinine binding site on each molecule of AAG. 3. Plasma AAG concentrations were consistently raised in acute malaria, and were higher in patients with cerebral malaria [2.03 (0.51) g l‐1, mean (s.d.)], and conscious patients with severe malaria [1.93 (0.53) g l‐1] than in patients with uncomplicated infections [1.55 (0.58) g l‐ 1], P = 0.008. Plasma protein binding of quinine was correspondingly higher and thus the proportion of free drug was lower in the severe groups; 5.5 (2.4)% compared with 7.2 (1.9)%, P = 0.03. 4. Following recovery from malaria, plasma AAG concentrations fell by an estimated 0.05 g l‐1 day‐1 to levels that were approximately half (median 45%) the admission value at 28 days. 5. AAG is the principal binding protein for quinine in plasma. Changes in plasma concentrations of this acute phase reactant account for the increased plasma protein binding of quinine in acute malaria. 1991 The British Pharmacological Society